Legal Measures Related to the Economic Activity of People with Disabilities in the Current Structure of the Labour Market - Roszewska, Katarzyna (Studia Oeconomica Posnaniensia, 2015)
Professional activity is one of the most important conditions for full inclusion and participation in society. However the form of legal solutions and support mechanisms for the employment of people with disabilities in Poland do not contribute to the desired level of increase in the level of employment, maintaining employment, or the return to the labour market. The paper identifies the main sources of law in force in Poland that effect the activity of persons with disabilities, but because of the limited scope of the paper, the primary objective is not their detailed presentation, but a discussion of selected legal measures aimed at activating people with disabilities. This analysis shows that the global legal solutions related to the professional activity of people with disabilities are within the international standards. However these solutions provide an insufficient range of individual support for people with disabilities. They also insufficiently take into account the changes in the labour market.